Metabolic engineering of plant monoterpenes, sesquiterpenes and diterpenes—current status and future opportunities. Issue 2 (21st November 2012) - Lange, B. Markus; Ahkami, Amirhossein
Summary Terpenoids (a.k.a. isoprenoids) represent the most diverse class of natural products found in plants, with tens of thousands of reported structures. Plant‐derived terpenoids have a multitude of pharmaceutical and industrial applications, but the natural resources for their extraction are often limited and, in many cases, synthetic routes are not commercially viable. Some of the most valuable terpenoids are not accumulated in model plants or crops, and genetic resources for breeding of terpenoid natural product traits are thus poorly developed. At present, metabolic engineering, either in the native producer or a heterologous host, is the only realistic alternative to improve yield and accessibility. In this review article, we will evaluate the state of the art of modulating the biosynthetic pathways for the production of mono‐, sesqui‐ and diterpenes in plants.